THE IMPACT OF EMOTION REGULATION ON AGGRESSIVE BEHAVIOR AMONG STUDENTS AT SMP NEGERI 19 JAMBI - Bellin Dwi Indah Cahya; Siti Amanah; Nur Hasanah Harahap; Zubaidah Zubaidah; Rully Andi Yaksa; Dian Wahyuningsih (Jurnal Bikotetik (Bimbingan dan Konseling : Teori dan Praktik), 2025)
This study aims to examine the influence of emotion regulation on aggressive behavior among students at SMP Negeri 19 Kota Jambi. The research employed a quantitative approach with an ex post facto design and involved 256 students selected through stratified random sampling. The research instruments consisted of an emotion regulation questionnaire (29 items) and an aggressive behavior questionnaire (26 items). The results showed that students’ emotion regulation levels were categorized as high (74.1%), while their aggressive behavior was categorized as moderate (56.4%). Regression analysis revealed a significance value of 0.000 with r = 0.468, indicating that emotion regulation contributed 46.8% to aggressive behavior. The better the students' ability to regulate their emotions, the lower their tendency to exhibit aggressive behavior. These findings highlight the importance of preventive Guidance and Counseling services in strengthening students’ emotion regulation to reduce the potential for aggressive behavior in the school environment